Isolation of Bhanja virus from ticks of the genus Haemaphysalis in southeast Bulgaria and presence of antibodies in pastured sheep - Pavlov, P; Rosický, B; Hubálek, Z; Daniel, M; Bárdos, V; Minár, J; Juricová, Z (Folia parasitologica, 1978)
Bhanja virus was isolated from ticks of the genus Haemaphysalis (H. punctata and H. sulcata) collected from sheep pastured in the surroundings of Akhtopol in southeast Bulgaria, and simultaneously blood sera of 58 sheep were investigated in plaque-reduction neutralization test with B lranja arbovirus. All sera contained antibodies to this virus in titres from 1:32 to 1:4096 (geometrical mean titre 1:494). The district of Akhtopol proved to be a natural focus of Bhanja virus.
Keywords: Arboviruses; Meningitis, Viral; meningoencefalitida; Animals; Ticks; nemoci ovcí; Sheep; zvířata; Antibodies, Viral; Bulgaria; arboviry; ovce; klíšťata; Bulharsko; Sheep Diseases; meningitida virová; Meningoencephalitis; protilátky virové